DETERMINANTES DA RESISTÊNCIA À EDUCAÇÃO A DISTÂNCIA (EAD): Uma pesquisa com alunos do Curso de Administração da UFF - Viana, Leonardo Gonçalves (2011)
One of limiting the expansion of courses offered through distance learning by Brazilian universities is the resistance of students on them in this mode. Thus, to investigate and ascertain the main reasons that lead the graduate student to resist the distance learning is the aim of this dissertation. Have endeavored to advance in this understanding of resistance mechanisms that affect the use of EAD. Data were collected through a non-probability survey among students of Business Administration from Universidade Federal Fluminense (UFF), because they had not attended courses in its graduate distance education in the sport and thus its resistance to EAD, in large measure, not based on prior experience in university studies. It was concluded that students have broad access to Information Technologies and Communication such as computers and broadband, widely use social networks, participate in discussion groups on the Internet mainly for entertainment purposes. There is also a widespread use of the Internet to conduct research school, but few had taken courses on the Internet. Ignorance about the student's distance learning suggests this is a possible source of resistance. The fluency of the student relationship with Information Technologies and Communication is one factor that reduces. Not knowing how to learn through distance education may increase the potential strength of this student to use the methodology. Students with experience in distance education have shown less resistance to this mode of those who have never taken a course in this mode.